Effect of Different Doses of Liquid Organic Fertilizer on the Growth of Lettuce Plants (Lactuca sativa L.): Pengaruh Perbedaan Dosis Pupuk Organik Cair Terhadap Pertumbuhan Tanaman Selada (Lactuca sativa L.) - Aditya, Haidar Fari; Permatasari, Fina Dwi (Journal of Applied Plant Technology, 2023)
Fertilization activities also provide macro and micro-nutrients for plants such as nitrogen, phosphorus, and potassium. The role of the three elements is very important and have mutually supporting functions in plant growth and development. This research aims to observe the effect of different doses of liquid organic fertilizer on the growth of lettuce plants. So, we can provide the best advice for fertilizing lettuce plants. Providing liquid organic fertilizer to 20 lettuce plants using 3 doses mixed with 1000 ml of water for each dose, including: (1) 5 ml dose of liquid organic fertilizer + 1000 ml water for five plants, (2) 10 ml dose of liquid organic fertilizer + 1000 ml of water for five plants, (3) Dose of 15 ml of liquid organic fertilizer + 1000 ml of water for five plants, and (4) Use of control on five plants that were not given POC. The results of the research showed that the effect of giving each dose of liquid organic fertilizer, namely 5 ml, 10 ml and 15 ml, showed the highest growth results, namely at a dose of 15 ml and the lowest was obtained in the treatment without liquid organic fertilizer (control).